SENSITIZING STUDENTS TO PRESCRIPTION WRITING BY CLINICAL CASE SCENARIO - ARUL AMUTHA ELIZABETH.L; S.V.MYTHILI; N.S.MUTHIAH (International Journal of Pharma and Bio Sciences, 2016)
Prescription writing is a core competency of a medical professional and it is the cornerstone for treatment. There is a worldwide concern regarding the lack of safe and rational prescribing skills and knowledge among the new medical graduates. This study is taken up in assessing the effectiveness of the prescription writing through clinical case scenario over the traditional tutorial based teaching. 85 students of 2nd M.B.B.S were exposed to the traditional teaching of prescription writing for myocardial infarction. Pre-test was conducted. Post-test was conducted after 3 weeks of small group discussion using paper cases of bronchial asthma to assess the effectiveness of case based teaching of prescription writing. The prescription was assessed using a checklist and scored accordingly (Physician component-2.5marks, Drug component-7.5 marks, total-10marks).The results obtained were statistically assessed using paired student‘t’ test. 85 students were evaluated in the prescription writing, and the scores in both pre-test and post-test was compared by paired students “t” test. And it was found that there was significant difference (p Ë‚0.001) in the prescription pattern in the students after teaching with clinical case scenario. The prescription skills and confidence of future doctors can be improved by teaching prescription using clinical case scenario rather than traditional tutorial method.